Development of a Stable MGAT1− CHO Cell Line to Produce Clade C gp120 With Improved Binding to Broadly Neutralizing Antibodies - Doran, Rachel C.; Yu, Bin; Wright, Meredith; O'Rourke, Sara M.; Yin, Lu; Richardson, Jennie M.; Byrne, Gabriel; Mesa, Kathryn A.; Berman, Phillip W. (Frontiers in Immunology, 2018)
The high rate of new HIV infections, particularly in Sub-Saharan Africa, emphasizes the need for a safe and effective vaccine to prevent acquired immunodeficiency syndrome (AIDS). To date, the only HIV vaccine trial that has exhibited protective efficacy in humans was the RV144 study completed in Thailand. The finding that protection correlated with antibodies to gp120 suggested that increasing the quality or magnitude of the antibody response that recognize gp120 might improve the modest yet significant protection (31.2%) achieved with this immunization regimen. However, the large-scale production of rgp120 suitable for clinical trials has been challenging due, in part, to low productivity and difficulties in purification. Moreover, the antigens that are currently available were produced largely by the same technology used in the early 1990s and fail to incorporate unique carbohydrates presented on HIV virions required for the binding of several major families of broadly neutralizing antibodies (bNAbs). Here we describe the development of a high-yielding CHO cell line expressing rgp120 from a clade C isolate (TZ97008), representative of the predominant circulating HIV subtype in Southern Africa and Southeast Asia. This cell line, produced using robotic selection, expresses high levels (1.2g/L) of the TZ97008 rgp120 antigen that incorporates oligomannose glycans required for binding to multiple glycan dependent bNAbs. The resulting rgp120 displays a lower degree of net charge and glycoform heterogeneity as compared to rgp120s produced in normal CHO cells. This homogeneity in net charge facilitates purification by filtration and ion exchange chromatography methods, eliminating the need for expensive custom-made lectin or immunoaffinity columns. The results described herein document the availability of a novel cell line for the large-scale production of clade C gp120 for clinical trials. Finally, the strategy used to produce a TZ97008 gp120 in the MGAT- CHO cell line can be applied to the production of other candidate HIV vaccines.